Administrasi Kurikulum dalam Pendidikan di Sekolah - Luthfi, Moh; Purwoyuliyanto, Heru (Lembaga Yasin AlSys, 2025)
This study was conducted at Madrasah Ibtidaiyah (MI) Blagung, Boyolali using a qualitative approach, involving the principal, teachers, and curriculum administration staff as research subjects. The aim of the study is to analyze the curriculum management and administration processes in supporting effective learning at the madrasah. Data were collected through interviews, observations, and documentation, and analyzed descriptively. The findings show that curriculum management is carried out through four main stages: planning, implementation, supervision, and evaluation. The planning stage involves designing learning programs based on students’ needs; the implementation stage focuses on the application of the curriculum in teaching and learning processes; the supervision stage ensures alignment between curriculum design and classroom practices; while the evaluation stage assesses the effectiveness of curriculum implementation and informs continuous improvement. Curriculum administration plays a strategic role in optimizing resource utilization, offering flexible learning options for students, and ensuring the efficiency and effectiveness of learning processes through systematic oversight. The study concludes that structured curriculum management, supported by sound administrative practices, is essential for achieving optimal educational outcomes in madrasahs.